Analysis of Social Change at Ciber Rescue, Cihideung Udik Village, Ciampea District, Bogor Regency - Putri, Dina Amanda; Kusuma, Fadilah Resti; Sinaga, Azaria Zulmahdiyyah; Raina, Thea; Purwandari, Heru; Rosidah, Wilda (AAI Pengda Riau, 2024)
Social movements serve the function of an organized collective effort to spark change. Social movements can be considered as driving tools that can push society towards new conditions, facing perceived challenges or needs. Social change is created from the success of social movements that bring about significant differences in community life. This research aims to examine the Ciber Rescue social movement as a driving factor for social change in the community of Cihideung Udik Village. The research was conducted using a qualitative approach through observation and in-depth interviews with informants. The research results show that Ciber Rescue is a community that plays a role in fulfilling social needs, operating at the individual, community, and societal levels, and has a positive influence on society, such as encouraging value changes, increasing collective awareness, fostering a spirit of mutual cooperation, and enhancing public knowledge about health and disaster management. Therefore, the Ciber Rescue community plays an important role, not only in social change within its community but also positively impacting the surrounding society